2020
DOI: 10.1371/journal.pone.0234738
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of jasmonate ZIM domain gene family in tuber mustard (Brassica juncea var. tumida)

Abstract: Tuber mustard, which is the raw material of Fuling pickle, is a crop with great economic value. However, during growth and development, tuber mustard is frequently attacked by the pathogen Plasmodiophora brassicae and frequently experiences salinity stress. Jasmonic acid (JA) is a hormone related to plant resistance to biotic and abiotic stress. Jasmonate ZIM domain proteins (JAZs) are crucial components of the JA signaling pathway and play important roles in plant responses to biotic and abiotic stress. To da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Several TIFY members were predicted to be located in organelles, such as chloroplasts and mitochondria ( Figure 1 ). These differences in cellular components indicate that the TIFY gene family developed in an extensive regulatory system in plant cells to control various processes ( Bai et al, 2011 ; Cai et al, 2020 ). Previous studies indicated that the members of the TIFY gene family are involved in various mechanisms of plant responses to stress and the regulation of plant growth and development ( Hakata et al, 2012 ; Zhou et al, 2015 ; Sun et al, 2017 ; Liu et al, 2020 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several TIFY members were predicted to be located in organelles, such as chloroplasts and mitochondria ( Figure 1 ). These differences in cellular components indicate that the TIFY gene family developed in an extensive regulatory system in plant cells to control various processes ( Bai et al, 2011 ; Cai et al, 2020 ). Previous studies indicated that the members of the TIFY gene family are involved in various mechanisms of plant responses to stress and the regulation of plant growth and development ( Hakata et al, 2012 ; Zhou et al, 2015 ; Sun et al, 2017 ; Liu et al, 2020 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse conditions, such as biotic and abiotic stresses, as limiting factors, affect plant performance. Previous studies revealed that members of the TIFY family, as specific plant TFs, play critical roles in regulating plant responses to adverse environmental conditions ( Ebel et al, 2018 ; Chao et al, 2019 ; Cai et al, 2020 ). For instance, overexpression of apple JAZ2 could significantly improve the tolerance to P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research identified 36, 38, 36, and 36 JAZ genes in B. rapa L. 40 , B. juncea var. tumida 41 , B. napus L. 42 , and B. oleracea var. capitata 30 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that no tandem duplication events of JAZ family genes were found in the B. rapa L. and B. juncea var. tumida 40 , 41 , whereas two pairs of tandem duplication genes were identified in Brassica oleracea var. capitata 30 .…”
Section: Discussionmentioning
confidence: 99%